Effect of Neurofeedback Interactions and Mental Imagery on the Elderly's Balance - Sima Moshref-Razavi; Mehdi Sohrabi; Mohammad Saber Sotoodeh (University of Social Welfare & Rehabilitation Sciences, 2017)
Objectives Balance maintenance is one of the indices of determining independence in older people. Identifying other factors that have considerable impact on the independence of older peoples is an interesting research topic. The present study aims at determining the effect of Neurofeedback and Mental Motor Imagery practices on balance in the elderly. Methods & Materials The population of this study consisted of elderly people of Mashhad, a city in northeast Iran. A total of 24 elderly people  with age ranging from 60-82 years old volunteered to participate in the study and were randomly assigned to three groups (with eight participants in each group). The participants of experimental groups were involved in the special training (neurofeedback training and mental imagery practice) for eight weeks (with three sessions each week)while the control group were not involved in any practice. Stork Balance Stand Test and Timed Up and Go (TUG) tests were used to assess the static and dynamic balance of participants respectively, before and after the training sessions. The Shapiro–Wilk test of normality was used to check normality of data. Additionally,  Analysis of Covariance (ANCOVA) was used to determine the effect of training with pre-test scores used as covariate. Statistical analysis was performed using SPSS Statistics 21 at a=0.05. Results The results of Analysis of Covariance revealed that there was a significant effect of neurofeedback and mental imagery on the static and dynamic balance of elderly people (P<0.05). Furthermore, neurofeedback had superior effect in both of the balance conditions (P<0.05). Conclusion The study recommends neurofeedback and mental motor imagery practices  to prevent balance loosing and improving balance ability in elderly people.